MAKING NATA DE CASSAVA FROM RENGGINANG LIQUID WASTE USING ACETOBACTER XYLIUM - Ahmad Shobib; Ery Fatarina; Jamal Adi Prasetiyo (Neo Teknika, 2019)
Processed cassava liquid waste in Nyamok Village causes a decrease in water quality with amarked unpleasant odor. The liquid waste comes from the washing process of raw materials andstarch deposited water containing starch. Glucose in cassava liquid waste can be a source of energyfor Acetobacter Xylinum to form cellulose called nata de cassava. This study examines the potential ofRengginang UKM liquid waste as a substrate / raw material for making nata de cassava as a newmaterial.Based on previous research, it was obtained optimization of various percentages of sugar(carbon source) and urea (nitrogen source). Therefore, this study aims to determine the optimizationof the percentage of sugar and urea given in fermentation by evaluating, among others, the test watercontent (moisture content), tensile strength test and elongation. The study was conducted with wastepreparation and processed into nata de cassava with variations of sugar and urea for 8 days offermentation. Wet nata de cassava thickness is measured to determine the optimal recipe. Thefermentation optimization results measured moisture content, dried and tested the tensile strength andelongation. The data obtained were tested statistically with two-way ANOVA. The results showed thatsugar and urea are very influential in the process of bacterial cellulose formation based on anova test,namely F Fc (11.8 2.9). The optimum conditions obtained are the addition of sugar 15 grams / Land urea 2 grams / L, with a thickness of 12.1 mm. Moisture content value of 97.97%, tensile strengthof 14.31 N/mm2 and elongation at 3.83%.Keyword: Nata de cassava, Urea,Sugar,Moisture content, Mensile strengt